Long-acting slow-release blended fertilizer and preparation method thereof

CN122977899APending Publication Date: 2026-10-27LIAONING WANYING AGRI SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611488367.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

二苯甲酮类光引发剂添加后会引入苯类物质,分解产生的苯类物质依然会对环境造成污染,过渡金属离子降解助剂中会使得土壤重金属污染

Benefits of technology

1.本发明采用合成促降解剂,配合破坏UV-944光稳定剂的活性循环与环状骨架,硅氧烷基共价锚定活性组分,结合分子的酸碱双催化位点,使土壤pH波动影响的机理,解决了缓释膜及光稳定剂土壤残留污染、促降解剂两端氨基改善与尿素的界面相容性问题和肥料难适应多土壤环境的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977899A_ABST
    Figure CN122977899A_ABST
Patent Text Reader

Abstract

The application discloses a long-acting slow-release mixed fertilizer and a preparation method thereof, and belongs to the technical field of fertilizers.The long-acting slow-release mixed fertilizer comprises urea, ammonium dihydrogen phosphate, potassium chloride, ammonium sulfate, trace element salt, magnesium phytate bridge-linked alginate salt nitrogen carrier zeolite, tannic acid zinc complex chitosan nitrification inhibition microcapsule, an anti-caking agent, degradable polyamide and a degradation-promoting agent; wherein the degradation-promoting agent is prepared through Boc amino protection, sulfide oxidation to generate a sulfone group, controllable monohydrolysis, acyl chloride to form a silicon ester, microwave Boc removal, and comprises a sulfone group, a double-end amino group and a siloxane structure.In order to solve the shortcomings of the prior art, a degradation-promoting agent is provided, the degradation-promoting agent is wrapped by a sulfone group and an acid-base cooperative site degradable polyamide film and destroys a UV944 light stabilizer skeleton; and covalent anchoring is realized by a siloxane group, so that the problems of difficult degradation and easy pollution of the light stabilizer are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fertilizer technology, and in particular to a long-acting slow-release blended fertilizer and its preparation method. Background Technology

[0002] Long-acting slow-release blended fertilizers are a new type of fertilizer made by uniformly blending fast-acting and slow-release nutrients. This type of fertilizer can achieve a stable supply of nutrients, with a nutrient utilization rate of over 30%. The fertilizer relies on a coating membrane structure to achieve a stable nutrient supply. By controlling the degradation rate or chemical bond breaking rate of the coating membrane, the nutrient release behavior can be controlled and regulated, thereby continuously supplying crops with essential nutrients such as nitrogen, phosphorus, and potassium, achieving the technical effect of slow nutrient release and long-term continuous fertilization. Among existing nitrogen source coating membranes, amide slow-release membranes are one of the main types used. Amide membranes have water absorption and retention properties, significantly improve fertilizer utilization, and reduce fertilizer waste and pollution.

[0003] To maintain the coating film's resistance to photodegradation, UV-944 light stabilizer is added to the amide film to improve the fertilizer's stability. However, UV-944 light stabilizer has a certain degree of stability and is difficult to degrade in the soil, thus preventing pollution.

[0004] To address the issue of the poor degradation of slow-release films containing UV-944 light stabilizers, a common method is to introduce degradation-promoting components. Common additives include benzophenone-based photoinitiators and transition metal ion degradation aids. However, the addition of benzophenone-based photoinitiators introduces benzene compounds, which still pollute the environment. Transition metal ion degradation aids can lead to heavy metal pollution in the soil. Therefore, developing a long-acting slow-release blended fertilizer to solve the problem of poor degradation and pollution caused by light stabilizers in slow-release films is of great significance. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a long-acting slow-release blended fertilizer and its preparation method.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A long-acting, slow-release blended fertilizer, characterized by comprising the following components in parts by weight: 28-36 parts by weight of urea, 18-24 parts by weight of ammonium dihydrogen phosphate, 16-22 parts by weight of potassium chloride, 6-10 parts by weight of ammonium sulfate, 2-4 parts by weight of magnesium sulfate monohydrate, 0.3-0.8 parts by weight of zinc sulfate monohydrate, 0.4-0.9 parts by weight of borax, 3-6 parts by weight of magnesium phytate-bridged alginate nitrogen-loaded zeolite, 2-5 parts by weight of zinc tannate complexed chitosan nitration inhibitor microcapsules, 0.2-0.6 parts by weight of anti-caking agent, 1.2-2.5 parts by weight of biodegradable polyamide, and 0.08-0.25 parts by weight of degradation promoter; The specific preparation method of the degradation promoter is as follows: S1: Dissolve 3-mercapto-1-propane and KH-550 in dichloromethane at 0~5℃, and add di-tert-butyl dicarbonate and triethylamine respectively. Stir continuously at 500~1000 rpm for 1 hour, wash with water and concentrate to obtain Boc-ONH-(CH2)3-SH and BocONH(CH2)3Si(OC2H5)3; S2: Dissolve the obtained Boc-ONH-(CH2)3-SH in anhydrous ethanol and add chloroacetic acid. Add potassium carbonate as a base to adjust the pH of the system to 8-9. Heat the system to 40-50℃ and stir continuously for 1 hour. Finally, adjust the pH of the system to 7.5-8 and extract and concentrate to obtain BocONH(CH2)3SCH2COOH. S3: Dissolve BocONH(CH2)3SCH2COOH in glacial acetic acid, control the temperature of the system at 30℃ and slowly add sufficient hydrogen peroxide dropwise, and stir continuously at a speed of 500~1000 rpm until the reaction is complete. Remove the solvent under reduced pressure to obtain BocONH(CH2)3SO2CH2COOH. S4: Dissolve the BocONH(CH2)3Si(OC2H5)3 obtained in S1 in anhydrous tetrahydrofuran, slowly add 1.0~1.2 eq of deionized water in an ice-water bath at 0℃, hydrolyze 1 part of ethoxy to obtain BocONH(CH2)3Si(OC2H5)2OH, and immediately remove trace amounts of water after the reaction is complete. S5: BocONH(CH2)3Si(OC2H5)2OH is cooled to -10~0℃ and oxaloyl chloride and DMF are added to obtain BocONH(CH2)3Si(OC2H5)2Cl. After concentrating and removing impurities at 0~5℃, it is dissolved in anhydrous dichloromethane and 2.2 eq of anhydrous triethylamine is added. This is then added dropwise to the BocONH(CH2)3SO2CH2COOH obtained in S3 to obtain the silicon ester product. S6: Dissolve the silicone ester product obtained in S5 in anhydrous acetonitrile, remove Boc by microwave with lithium chloride under nitrogen protection for 1 hour, and then distill under reduced pressure to obtain the degradation promoter.

[0007] Preferably, the chemical structural formula of the degradation promoter is H2N-CH2-CH2-CH2-SO2-CH2-C(=O)-O-Si(OCH3)2-CH2CH2CH2-NH2, which contains sulfone, amino, and siloxane groups. The degradation promoter has amino groups at both ends, and the degradation promoter with amino groups has a certain compatibility when coated with urea, effectively alleviating the problem of incompatibility between the degradation promoter and urea.

[0008] Preferably, the degradation promoter contains sulfone groups. When excited, the sulfone groups generate active free radicals that attack the fatty amide and fatty ester segments on the degradable polyamide backbone, causing the polymer backbone to break down into smaller molecular fragments. When excited, the free radicals of the sulfone groups preferentially react with the nitric oxide free radicals of UV-944, consuming the core active sites of UV-944. The free radicals generated by the sulfone groups react with the tertiary amine sites on the tetramethylpiperidine ring in the UV-944 molecule, destroying the six-membered ring skeleton structure. Under soil moisture conditions, the degradation promoter locally forms a slightly acidic environment, hydrolyzing and breaking the amide and other structures within the UV-944 molecule, thus eliminating the long-term residual pollution of UV-944.

[0009] Preferably, the siloxane group in the degradation promoter molecule can undergo hydrolysis to generate silanol groups, which can undergo silanization covalent bonding with the terminal hydroxyl / carboxyl groups of the amide and ester bonds on the degradable polyamide molecular chain, so that the degradation promoter is firmly grafted and fixed inside the slow-release membrane matrix, and will not be easily dissolved and lost with rainwater, ensuring the long-lasting degradation promotion effect.

[0010] Preferably, the molecules release free amino and carboxyl groups through the soil medium; the amino group is an alkaline site and the carboxyl group is an acidic site, which achieves intramolecular acid-base synergistic catalysis under soil moisture conditions, accelerates the hydrolysis and breakage of amide and ester bonds in polyamide, and promotes the gradual destruction of the slow-release coating and its additives; at the same time, the degraded small molecule fragments can be further completely mineralized under the action of soil microorganisms.

[0011] Preferably, the degradation promoter is placed in the core of the slow-release nitrogen source particle. After the nitrogen source is released, the degradation promoter in the core continues to act on the remaining coating layer to achieve coating degradation, thus avoiding long-term residue of the coating and additives in the soil and damage to the soil and soil microbial environment.

[0012] Preferably, the particle size of the urea, ammonium dihydrogen phosphate, potassium chloride, ammonium sulfate, magnesium sulfate monohydrate, and zinc sulfate monohydrate is 2.0~4.0 mm.

[0013] Preferably, the main chain of the biodegradable polyamide contains both aliphatic amide segments and aliphatic ester segments.

[0014] Preferably, the 3-mercapto-1-propane and di-tert-butyl dicarbonate are mixed in a molar ratio of 1:(1~1.2) and KH-550 and di-tert-butyl dicarbonate are mixed in a molar ratio of 1:(1~1.2).

[0015] Preferably, the amount of oxaloyl chloride added is 1 to 1.2 eq of BocONH(CH2)3Si(OC2H5)2OH.

[0016] Preferably, the microwave Boc removal setting includes a microwave reactor power of 250~300W, a temperature control of 130~140℃, a pressure limit of 12~14bar, a stirring speed of 400~600rpm, and a microwave reaction time of 60min.

[0017] Furthermore, a method for preparing a long-acting, slow-release blended fertilizer includes the following steps: (1) The degradation promoter is used as the core and put into a fluidized bed coating machine. Molten liquid urea is sprayed into the fluidized bed and continuously coated with the inner layer of urea on the outside of the degradation promoter particles. After the inner layer of urea is coated, the particles are cooled and solidified. The fluidized bed is kept in a fluidized state. The biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The solution is sprayed onto the outer surface of the inner layer of urea. The solvent evaporates to form a film, resulting in slow-release nitrogen source particles with the degradation promoter core, urea coating inner layer, and biodegradable polyamide slow-release film outer layer in sequence from the inside to the outside. (2) The slow-release nitrogen source particles, ammonium dihydrogen phosphate, potassium chloride, ammonium sulfate, magnesium sulfate monohydrate, zinc sulfate monohydrate, borax, magnesium phytate-bridged alginate nitrogen-supported zeolite, and zinc tannate complexed chitosan nitration inhibitor microcapsules are thoroughly mixed, sieved, and graded for premixing. (3) Transfer the graded and premixed material into a low-speed horizontal mixer, control the stirring speed at 25~35r / min, add fertilizer-specific anti-caking agent, continue mixing for 8~12min, discharge and screen to obtain long-acting slow-release blended fertilizer.

[0018] Preferably, (1) the atomization pressure of the fluidized bed coating machine is 0.30~0.45MPa, and when preparing the coating solution, the mass ratio of degradable polyamide, dichloromethane and ethanol is (8~12):(75~82):(8~12).

[0019] Preferably, (1) the slow-release nitrogen source particles obtained have the following components from the inside out: the core of the degradation promoter accounts for 0.5 to 1.8 wt% of the total mass of the slow-release nitrogen source particles, the inner layer of urea accounts for 88 to 93 wt% of the total mass of the slow-release nitrogen source particles, and the outer layer of the biodegradable polyamide slow-release membrane accounts for 4 to 9.5 wt% of the total mass of the slow-release nitrogen source particles.

[0020] Preferably, in step (2), each fertilizer particle is screened before grading and premixing to remove particles with a particle size of <2.0 mm and >4.0 mm. The grading and premixing process involves premixing slow-release nitrogen source particles with phytic acid magnesium-bridged alginate nitrogen-supported zeolite and zinc tannin complexed chitosan nitration inhibitor microcapsules to obtain functional particle mixture, and then mixing the functional particle mixture with the remaining basic fertilizer particles.

[0021] Preferably, the degradation promoter molecule contains an amino group at its terminal position. The amino group can form hydrogen bonds with urea, which enables good compatibility between the core and the molten urea coating layer, and avoids voids and cracks at the urea layer interface.

[0022] Preferably, the degradation promoter does not produce benzene ring-containing degradation products like those found in traditional benzophenones, nor does it accumulate transition metal salts. The molecular skeleton of this degradation promoter is composed of C, H, O, N, S, and Si, and does not contain heavy metals or benzene rings. After degradation, it decomposes into small molecular fragments containing nitrogen, sulfur, and silicon. The N and S in the decomposition products can be used as micronutrients in the soil, and the silicon components can be converted into silicates. There is no risk of toxicity from the degradation products. At the same time, the molecules generated by the hydrolysis of the degradation promoter have both acid and base sites, and are not dependent on the pH changes of the soil itself, making it applicable to a wide range of regions.

[0023] Preferably, the nitrogen source will not react with the phytic acid magnesium-bridged alginate nitrogen-supported zeolite and zinc tannin complex chitosan structure in the system, and will not cause premature deactivation of nitration inhibitors. It is compatible with the functions of promoting degradation, inhibiting nitration, and adsorbing and storing nitrogen sources.

[0024] Preferably, the slow-release nitrogen source granules are compounded with ammonium dihydrogen phosphate, potassium chloride, ammonium sulfate, magnesium sulfate monohydrate, zinc sulfate monohydrate, and borax. This combination can synergistically supply macronutrients such as nitrogen, phosphorus, and potassium, as well as micronutrients such as magnesium, zinc, and boron. This achieves a fertilization mode that provides fast-acting nutrients to meet the seedling growth needs of crops and slow-release nitrogen sources to match the nutrient requirements of crops in the middle and later stages. Combined with magnesium phytate-bridged alginate nitrogen-supported zeolite, the porous adsorption properties of the zeolite help to retain nitrogen and potassium nutrients, reduce leaching loss, and assist in slow-release fertilization. At the same time, it improves the soil's water and fertilizer retention capacity. Zinc tannin complexed with chitosan nitrification inhibitory microcapsules can delay the ammonium nitrogen nitrification process, reduce nitrogen denitrification loss, improve nitrogen fertilizer utilization, and slowly release zinc, while also having a certain antibacterial and growth-promoting effect. The materials are screened and premixed in a graded manner to effectively avoid the problem of stratification and segregation caused by differences in particle size between different particles. This ensures that all fertilizer components are mixed evenly, resulting in a balanced nutrient supply in the field after fertilization. Moreover, all functional components are degradable and will not cause residual soil pollution.

[0025] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses a synthetic degradation promoter to disrupt the active cycle and cyclic framework of UV-944 light stabilizer. The active component is covalently anchored by siloxane and bound to the acid-base dual catalytic sites of the molecule. This addresses the mechanism by which soil pH fluctuations affect the slow-release membrane and light stabilizer soil residue pollution, the interfacial compatibility issues between the amino groups at both ends of the degradation promoter and urea, and the difficulty of fertilizer adapting to various soil environments.

[0026] 2. This invention uses di-tert-butyl dicarbonate as a protecting group, which solves the problem of amino groups easily reacting with subsequent groups, reduces side reactions, improves product utilization, and solves the problem of diversified reactions of multiple active groups in the reactants.

[0027] 3. This invention uses peroxide as an oxide, and the peroxide reacts with the thioether bond to generate a sulfone bond, thus enabling the additive to contain a sulfone functional group, which gives the additive the ability to decompose UV-944 and polyamide, while also enabling the molecules generated by the hydrolysis of the degradation promoter to have both acid and base sites.

[0028] 4. This invention uses oxalyl chloride as a reactant, which reacts with a substance containing silanol groups to generate a product containing silanol chloride, which then reacts with a subsequent carboxylic acid to generate a degradation promoter for the target product, thereby achieving highly selective synthesis of the degradation promoter for the target product.

[0029] 5. This invention uses a nitrogen source to coat a degradation promoter. After the complete release of the slow-release nitrogen source, the degradation promoter promotes the decomposition of the coating film, accelerates the hydrolytic breakage of amide bonds and ester bonds in polyamide, and promotes the degradation and mineralization of the slow-release coating film and its additives. Attached Figure Description

[0030] Figure 1 This is a process flow diagram of a long-acting slow-release blended fertilizer and its preparation method proposed in this invention. Detailed Implementation

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0032] Example 1: A long-acting slow-release blended fertilizer and its preparation method, comprising the following steps: S1: Dissolve 10.2 kg of 3-mercapto-1-propane and 23.0 kg of KH-550 in dichloromethane at 0~5℃, and add 27.2 kg of di-tert-butyl dicarbonate and 19.2 kg of triethylamine to each. Stir continuously at 500 rpm for 1 hour, wash with water and concentrate to obtain Boc-ONH-(CH2)3-SH and BocONH(CH2)3Si(OC2H5)3; S2: Dissolve 20.2 kg of Boc-ONH-(CH2)3-SH in 230 L of anhydrous ethanol and add 9.5 kg of chloroacetic acid. Add 13.0 kg of potassium carbonate as a base to adjust the pH of the system to 8. Heat the system to 40 °C and stir continuously for 1 hour. Finally, adjust the pH of the system to 7.5 and extract and concentrate to obtain BocONH(CH2)3SCH2COOH. S3: Dissolve 23.0 kg of BocONH(CH2)3SCH2COOH in 170 L of glacial acetic acid, control the temperature of the system at 30 °C and slowly add 21.2 kg of 30% hydrogen peroxide by mass, stirring continuously at 500 rpm until the reaction is complete, and remove the solvent under reduced pressure to obtain BocONH(CH2)3SO2CH2COOH. S4: Dissolve 23.5 kg of BocONH(CH2)3Si(OC2H5)3 obtained in S1 in 200 L of anhydrous tetrahydrofuran, and slowly add 1.38 kg of deionized water in an ice-water bath at 0 °C. Hydrolyze 1 part of ethoxy to obtain BocONH(CH2)3Si(OC2H5)2OH. Remove trace amounts of water immediately after the reaction is complete. S5: Take 22.6 kg of BocONH(CH2)3Si(OC2H5)2OH, cool it to -10~0℃, and add 10.0 kg of oxaloyl chloride and 0.25 kg of DMF to obtain BocONH(CH2)3Si(OC2H5)2Cl. After concentrating and removing impurities at 0~5℃, dissolve it in anhydrous dichloromethane and add 14.3 kg of anhydrous triethylamine. Add it dropwise to the 22.3 kg of BocONH(CH2)3SO2CH2COOH obtained in S3 to obtain the silicon ester product. S6: Dissolve 34.2 kg of the silicone ester product obtained in S5 in 240 L of anhydrous acetonitrile, remove Boc with 7.9 kg of lithium chloride in a microwave oven under nitrogen protection at 250 W and 130 °C for 1 hour, and then distill under reduced pressure to obtain the degradation promoter. S7: The degradation promoter is used as the core and fed into a fluidized bed coating machine. Molten liquid urea is atomized and sprayed into the fluidized bed coating machine at an atomization pressure of 0.3 MPa to form a core of 1.8 wt% degradation promoter and 88.7 wt% slow-release nitrogen source. After the particles are cooled and solidified, the biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The mass ratio of biodegradable polyamide, dichloromethane and ethanol in the coating solution is 8:82:8. The solution is atomized and sprayed onto the outer surface of the inner layer of urea to form a slow-release film of 9.5 wt% to obtain slow-release nitrogen source particles. S8: Thoroughly mix, sieve, and grade the following ingredients: 28 kg slow-release nitrogen source granules, 18 kg ammonium dihydrogen phosphate, 16 kg potassium chloride, 6 kg ammonium sulfate, 2 kg magnesium sulfate monohydrate, 0.3 kg zinc sulfate monohydrate, 0.4 kg borax, 3 kg magnesium phytate-bridged alginate nitrogen-supported zeolite, and 2 kg zinc tannate complexed chitosan nitration inhibitor microcapsules; S9: Transfer the graded and premixed materials into a low-speed horizontal mixer, control the stirring speed at 25 r / min, add 0.2 kg of fertilizer-specific anti-caking agent, continue mixing for 8 min, and screen the discharged material to obtain particles of 2.0~4.0 mm to obtain a long-acting slow-release blended fertilizer.

[0033] Example 2: A long-acting slow-release blended fertilizer and its preparation method, comprising the following steps: S1: Dissolve 11.2 kg of 3-mercapto-1-propane and 25.6 kg of KH-550 in dichloromethane at 0~5℃, and add 30.4 kg of di-tert-butyl dicarbonate and 21.3 kg of triethylamine to each. Stir continuously at 1000 rpm for 1 hour, wash with water and concentrate to obtain Boc-ONH-(CH2)3-SH and BocONH(CH2)3Si(OC2H5)3; S2: Dissolve 22.2 kg of Boc-ONH-(CH2)3-SH in 270 L of anhydrous ethanol and add 11.0 kg of chloroacetic acid. Add 15.0 kg of potassium carbonate as a base to adjust the pH of the system to 8. Heat the system to 50 °C and stir continuously for 1 hour. Finally, adjust the pH of the system to 8 and extract and concentrate to obtain BocONH(CH2)3SCH2COOH. S3: Dissolve 25.4 kg of BocONH(CH2)3SCH2COOH in 190 L of glacial acetic acid, control the temperature of the system at 30 °C and slowly add 22.5 kg of 30% hydrogen peroxide by mass, and stir continuously at 1000 rpm until the reaction is complete. Remove the solvent under reduced pressure to obtain BocONH(CH2)3SO2CH2COOH. S4: Dissolve 25.4 kg of BocONH(CH2)3Si(OC2H5)3 obtained in S1 in 240 L of anhydrous tetrahydrofuran, and slowly add 1.49 kg of deionized water in an ice-water bath at 0 °C to hydrolyze 1 part of ethoxy to obtain BocONH(CH2)3Si(OC2H5)2OH. Remove trace amounts of water immediately after the reaction is complete. S5: Take 25.0 kg of BocONH(CH2)3Si(OC2H5)2OH, cool it to -10~0℃, and add 11.0 kg of oxaloyl chloride and 0.35 kg of DMF to obtain BocONH(CH2)3Si(OC2H5)2Cl. After concentrating and removing impurities at 0~5℃, dissolve it in anhydrous dichloromethane and add 15.8 kg of anhydrous triethylamine. Add it dropwise to the 24.7 kg of BocONH(CH2)3SO2CH2COOH obtained in S3 to obtain the silicon ester product. S6: Dissolve 37.8 kg of the silicone ester product obtained in S5 in 280 L of anhydrous acetonitrile, remove Boc with 9.2 kg of lithium chloride in a microwave oven under nitrogen protection at 250 W and 130 °C for 1 hour, and then distill under reduced pressure to obtain the degradation promoter. S7: The degradation promoter is used as the core and fed into a fluidized bed coating machine. Molten liquid urea is atomized and sprayed into the fluidized bed coating machine at an atomization pressure of 0.45 MPa to form a core of 1.8 wt% degradation promoter and 93 wt% slow-release nitrogen source. After the particles cool and solidify, the biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The mass ratio of biodegradable polyamide, dichloromethane and ethanol in the coating solution is 12:75:12. The solution is atomized and sprayed onto the outer surface of the inner layer of urea to form a slow-release film of 5.2 wt%, thus obtaining slow-release nitrogen source particles. S8: Thoroughly mix, sieve, and grade the following ingredients: 36 kg slow-release nitrogen source granules, 24 kg ammonium dihydrogen phosphate, 22 kg potassium chloride, 10 kg ammonium sulfate, 4 kg magnesium sulfate monohydrate, 0.8 kg zinc sulfate monohydrate, 0.9 kg borax, 6 kg magnesium phytate-bridged alginate nitrogen-supported zeolite, and 5 kg zinc tannate complexed chitosan nitration inhibitor microcapsules; S9: Transfer the graded and premixed materials into a low-speed horizontal mixer, control the stirring speed at 35 r / min, add 0.2 kg of fertilizer-specific anti-caking agent, continue mixing for 12 min, and screen the discharged material to obtain particles of 2.0~4.0 mm to obtain a long-acting slow-release blended fertilizer.

[0034] Example 3: A long-acting slow-release blended fertilizer and its preparation method, comprising the following steps: S1: Dissolve 8.3 kg of 3-mercapto-1-propane and 19.7 kg of KH-550 in dichloromethane at 0~5℃, and add 21.8 kg of di-tert-butyl dicarbonate and 20.2 kg of triethylamine to each. Stir continuously at 1000 rpm for 1 hour, wash with water and concentrate to obtain Boc-ONH-(CH2)3-SH and BocONH(CH2)3Si(OC2H5)3; S2: Dissolve 21.2 kg of Boc-ONH-(CH2)3-SH in 250 L of anhydrous ethanol and add 8 kg of chloroacetic acid. Add 14 kg of potassium carbonate as a base to adjust the pH of the system to 7.8. Heat the system to 45 °C and stir continuously for 1 hour. Finally, adjust the pH of the system to 7.8 and extract and concentrate to obtain BocONH(CH2)3SCH2COOH. S3: Dissolve 24.2 kg of BocONH(CH2)3SCH2COOH in 180 L of glacial acetic acid, control the temperature of the system at 30 °C and slowly add 21.0 kg of 30% hydrogen peroxide by mass, stirring continuously at 1000 rpm until the reaction is complete, and remove the solvent under reduced pressure to obtain BocONH(CH2)3SO2CH2COOH. S4: Dissolve 24.2 kg of BocONH(CH2)3Si(OC2H5)3 obtained in S1 in 220 L of anhydrous tetrahydrofuran, and slowly add 1.42 kg of deionized water in an ice-water bath at 0 °C to hydrolyze 1 part of ethoxy to obtain BocONH(CH2)3Si(OC2H5)2OH. Remove trace amounts of water immediately after the reaction is complete. S5: Take 23.8 kg of BocONH(CH2)3Si(OC2H5)2OH, cool it to -10~0℃, and add 10.3 kg of oxaloyl chloride and 0.3 kg of DMF to obtain BocONH(CH2)3Si(OC2H5)2Cl. After concentrating and removing impurities at 0~5℃, dissolve it in anhydrous dichloromethane and add 15 kg of anhydrous triethylamine. Add it dropwise to the BocONH(CH2)3SO2CH2COOH obtained in S3 to obtain the silicon ester product. S6: Dissolve 36 kg of the silicone ester product obtained in S5 in 260 L of anhydrous acetonitrile, remove Boc with 8.34 kg of lithium chloride in a microwave oven under nitrogen protection at 250 W and 130 °C for 1 hour, and then distill under reduced pressure to obtain the degradation promoter. S7: The degradation promoter is used as the core and fed into a fluidized bed coating machine. Molten liquid urea is atomized and sprayed into the fluidized bed coating machine at an atomization pressure of 0.37 MPa to form a core of 1.2 wt% degradation promoter and 90 wt% slow-release nitrogen source. After the particles cool and solidify, the biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The mass ratio of biodegradable polyamide, dichloromethane and ethanol in the coating solution is 12:75:12. The solution is atomized and sprayed onto the outer surface of the inner layer of urea to form a slow-release film of 8.8 wt%, thus obtaining slow-release nitrogen source particles. S8: Thoroughly mix, sieve, and grade the following ingredients: 33 kg slow-release nitrogen source granules, 20 kg ammonium dihydrogen phosphate, 18 kg potassium chloride, 9 kg ammonium sulfate, 3 kg magnesium sulfate monohydrate, 0.5 kg zinc sulfate monohydrate, 0.6 kg borax, 5 kg magnesium phytate-bridged alginate nitrogen-supported zeolite, and 3 kg zinc tannate complexed chitosan nitration inhibitor microcapsules; S9: Transfer the graded and premixed materials into a low-speed horizontal mixer, control the stirring speed at 30 r / min, add 0.2 kg of fertilizer-specific anti-caking agent, continue mixing for 10 min, and screen the discharged material to obtain particles of 2.0~4.0 mm to obtain a long-acting slow-release blended fertilizer.

[0035] Comparative Example 1: Based on Example 2, the difference is that the protection of the amino group is missing.

[0036] S1: Dissolve 11.2 kg of 3-mercapto-1-propane in 270 L of anhydrous ethanol and add 11.9 kg of chloroacetic acid. Add 15.0 kg of potassium carbonate as a base to adjust the pH of the system to 8. Heat the system to 50 °C and stir continuously for 1 hour. Finally, adjust the pH of the system to 8 and extract and concentrate to obtain NH2(CH2)3SCH2COOH. S2: Dissolve 15 kg of NH2(CH2)3SCH2COOH in 190 L of glacial acetic acid, control the temperature of the system at 30 °C and slowly add 22.5 kg of 30% hydrogen peroxide by mass, stirring continuously at 1000 rpm until the reaction is complete, and remove the solvent under reduced pressure to obtain NH2(CH2)3SO2CH2COOH. S3: Dissolve 27.0 kg of NH2(CH2)3Si(OC2H5)3 in 240 L of anhydrous tetrahydrofuran, slowly add 2.4 kg of deionized water dropwise in an ice-water bath at 0 °C, hydrolyze 1 part of ethoxy to obtain NH2(CH2)3Si(OC2H5)2OH, and immediately remove trace amounts of water after the reaction is complete; S4: Take 20.0 kg of NH2(CH2)3Si(OC2H5)2OH, cool it to -10~0℃, and add 11.0 kg of oxaloyl chloride and 0.35 kg of DMF to obtain NH2(CH2)3Si(OC2H5)2Cl. After concentrating and removing impurities at 0~5℃, dissolve it in anhydrous dichloromethane and add 15.8 kg of anhydrous triethylamine. Add it dropwise to 15.0 kg of NH2(CH2)3SO2CH2COOH obtained in S3 to obtain the silicon ester product. S5: The degradation promoter is used as the core and fed into a fluidized bed coating machine. Molten liquid urea is atomized and sprayed into the fluidized bed coating machine at an atomization pressure of 0.45 MPa to form a core of 1.8 wt% degradation promoter and 93 wt% slow-release nitrogen source. After the particles cool and solidify, the biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The mass ratio of biodegradable polyamide, dichloromethane and ethanol in the coating solution is 12:75:12. The solution is atomized and sprayed onto the outer surface of the inner layer of urea to form a slow-release film of 5.2 wt%, thus obtaining slow-release nitrogen source particles. S6: Thoroughly mix, sieve, and grade the following ingredients: 36 kg slow-release nitrogen source granules, 24 kg ammonium dihydrogen phosphate, 22 kg potassium chloride, 10 kg ammonium sulfate, 4 kg magnesium sulfate monohydrate, 0.8 kg zinc sulfate monohydrate, 0.9 kg borax, 6 kg magnesium phytate-bridged alginate nitrogen-supported zeolite, and 5 kg zinc tannate complexed chitosan nitration inhibitor microcapsules; S7: Transfer the graded and premixed materials into a low-speed horizontal mixer, control the stirring speed at 35 r / min, add 0.2 kg of fertilizer-specific anti-caking agent, continue mixing for 12 min, and screen the output to obtain particles of 2.0~4.0 mm to obtain a long-acting slow-release blended fertilizer.

[0037] Comparative Example 2: Based on Example 2, the difference is that hydrogen peroxide was not added.

[0038] S1: Dissolve 11.2 kg of 3-mercapto-1-propane and 25.6 kg of KH-550 in dichloromethane at 0~5℃, and add 30.4 kg of di-tert-butyl dicarbonate and 21.3 kg of triethylamine to each. Stir continuously at 1000 rpm for 1 hour, wash with water and concentrate to obtain Boc-ONH-(CH2)3-SH and BocONH(CH2)3Si(OC2H5)3; S2: Dissolve 22.2 kg of Boc-ONH-(CH2)3-SH in 270 L of anhydrous ethanol and add 11.0 kg of chloroacetic acid. Add 15.0 kg of potassium carbonate as a base to adjust the pH of the system to 8. Heat the system to 50 °C and stir continuously for 1 hour. Finally, adjust the pH of the system to 8 and extract and concentrate to obtain BocONH(CH2)3SCH2COOH. S3: Dissolve 25.4 kg of BocONH(CH2)3Si(OC2H5)3 obtained in S1 in 240 L of anhydrous tetrahydrofuran, and slowly add 1.49 kg of deionized water in an ice-water bath at 0 °C. Hydrolyze 1 part of ethoxy to obtain BocONH(CH2)3Si(OC2H5)2OH. Remove trace amounts of water immediately after the reaction is complete. S4: Take 25.0 kg of BocONH(CH2)3Si(OC2H5)2OH, cool it to -10~0℃, and add 11.0 kg of oxaloyl chloride and 0.35 kg of DMF to obtain BocONH(CH2)3Si(OC2H5)2Cl. After concentrating and removing impurities at 0~5℃, dissolve it in anhydrous dichloromethane and add 15.8 kg of anhydrous triethylamine. Add it dropwise to the BocONH(CH2)3SCH2COOH obtained in S2 to obtain the silicon ester product. S5: Dissolve 33 kg of the silicone ester product obtained in S4 in 280 L of anhydrous acetonitrile, remove Boc by microwave with 9.2 kg of lithium chloride under nitrogen protection at 250 W and 130 °C for 1 hour, and distill under reduced pressure to obtain a sulfone-free degradation promoter. S6: The degradation promoter is used as the core and fed into a fluidized bed coating machine. Molten liquid urea is atomized and sprayed into the fluidized bed coating machine at an atomization pressure of 0.45 MPa to form a core of 1.8 wt% degradation promoter and 93 wt% slow-release nitrogen source. After the particles cool and solidify, the biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The mass ratio of biodegradable polyamide, dichloromethane and ethanol in the coating solution is 12:75:12. The solution is atomized and sprayed onto the outer surface of the inner layer of urea to form a slow-release film of 5.2 wt%, thus obtaining slow-release nitrogen source particles. S7: Thoroughly mix, sieve, and grade the following ingredients: 36 kg slow-release nitrogen source granules, 24 kg ammonium dihydrogen phosphate, 22 kg potassium chloride, 10 kg ammonium sulfate, 4 kg magnesium sulfate monohydrate, 0.8 kg zinc sulfate monohydrate, 0.9 kg borax, 6 kg magnesium phytate-bridged alginate nitrogen-supported zeolite, and 5 kg zinc tannate complexed chitosan nitration inhibitor microcapsules; S8: Transfer the graded and premixed materials into a low-speed horizontal mixer, control the stirring speed at 35 r / min, add 0.2 kg of fertilizer-specific anti-caking agent, continue mixing for 12 min, and screen the output to obtain particles of 2.0~4.0 mm to obtain a long-acting slow-release blended fertilizer.

[0039] Comparative Example 3: Based on Example 2, the difference is that excess deionized water is used for hydrolysis.

[0040] S1: Dissolve 11.2 kg of 3-mercapto-1-propane and 25.6 kg of KH-550 in dichloromethane at 0~5℃, and add 30.4 kg of di-tert-butyl dicarbonate and 21.3 kg of triethylamine to each. Stir continuously at 1000 rpm for 1 hour, wash with water and concentrate to obtain Boc-ONH-(CH2)3-SH and BocONH(CH2)3Si(OC2H5)3; S2: Dissolve 22.2 kg of Boc-ONH-(CH2)3-SH in 270 L of anhydrous ethanol and add 11.0 kg of chloroacetic acid. Add 15.0 kg of potassium carbonate as a base to adjust the pH of the system to 8. Heat the system to 50 °C and stir continuously for 1 hour. Finally, adjust the pH of the system to 8 and extract and concentrate to obtain BocONH(CH2)3SCH2COOH. S3: Dissolve 25.4 kg of BocONH(CH2)3SCH2COOH in 190 L of glacial acetic acid, control the temperature of the system at 30 °C and slowly add 22.5 kg of 30% hydrogen peroxide by mass, and stir continuously at 1000 rpm until the reaction is complete. Remove the solvent under reduced pressure to obtain BocONH(CH2)3SO2CH2COOH. S4: Dissolve 25.4 kg of BocONH(CH2)3Si(OC2H5)3 obtained in S1 in 240 L of anhydrous tetrahydrofuran, and slowly add 4.2 kg of deionized water dropwise in an ice-water bath at 0 °C to hydrolyze the ethoxy group to obtain BocONH(CH2)3Si(OH)3. Remove trace amounts of water immediately after the reaction is complete. S5: Take 20.0 kg of BocONH(CH2)3Si(OH)3, cool it to -10~0℃, and add 42 kg of oxalyl chloride and 0.35 kg of DMF to obtain BocONH(CH2)3Si(OH)2Cl. After concentrating and removing impurities at 0~5℃, dissolve it in anhydrous dichloromethane and add 15.8 kg of anhydrous triethylamine. Add it dropwise to S3 to obtain 24.7 kg of BocONH(CH2)3SO2CH2COOH. S6: Dissolve the product obtained in S5 in 280L of anhydrous acetonitrile, remove Boc by microwave with 9.2kg of lithium chloride under nitrogen protection at 250W and 130℃ for 1 hour, and then distill under reduced pressure to obtain the degradation promoter. S7: The degradation promoter is used as the core and fed into a fluidized bed coating machine. Molten liquid urea is atomized and sprayed into the fluidized bed coating machine at an atomization pressure of 0.45 MPa to form a core of 1.8 wt% degradation promoter and 93 wt% slow-release nitrogen source. After the particles cool and solidify, the biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The mass ratio of biodegradable polyamide, dichloromethane and ethanol in the coating solution is 12:75:12. The solution is atomized and sprayed onto the outer surface of the inner layer of urea to form a slow-release film of 5.2 wt%, thus obtaining slow-release nitrogen source particles. S8: Thoroughly mix, sieve, and grade the following ingredients: 36 kg slow-release nitrogen source granules, 24 kg ammonium dihydrogen phosphate, 22 kg potassium chloride, 10 kg ammonium sulfate, 4 kg magnesium sulfate monohydrate, 0.8 kg zinc sulfate monohydrate, 0.9 kg borax, 6 kg magnesium phytate-bridged alginate nitrogen-supported zeolite, and 5 kg zinc tannate complexed chitosan nitration inhibitor microcapsules; S9: Transfer the graded and premixed materials into a low-speed horizontal mixer, control the stirring speed at 35 r / min, add 0.2 kg of fertilizer-specific anti-caking agent, continue mixing for 12 min, and screen the output to obtain particles of 2.0~4.0 mm to obtain a long-acting slow-release blended fertilizer.

[0041] Comparative Example 4: Based on Example 2, the difference is that microwave de-Boc is missing.

[0042] S1: Dissolve 11.2 kg of 3-mercapto-1-propane and 25.6 kg of KH-550 in dichloromethane at 0~5℃, and add 30.4 kg of di-tert-butyl dicarbonate and 21.3 kg of triethylamine to each. Stir continuously at 1000 rpm for 1 hour, wash with water and concentrate to obtain Boc-ONH-(CH2)3-SH and BocONH(CH2)3Si(OC2H5)3; S2: Dissolve 22.2 kg of Boc-ONH-(CH2)3-SH in 270 L of anhydrous ethanol and add 11.0 kg of chloroacetic acid. Add 15.0 kg of potassium carbonate as a base to adjust the pH of the system to 8. Heat the system to 50 °C and stir continuously for 1 hour. Finally, adjust the pH of the system to 8 and extract and concentrate to obtain BocONH(CH2)3SCH2COOH. S3: Dissolve 25.4 kg of BocONH(CH2)3SCH2COOH in 190 L of glacial acetic acid, control the temperature of the system at 30 °C and slowly add 22.5 kg of 30% hydrogen peroxide by mass, and stir continuously at 1000 rpm until the reaction is complete. Remove the solvent under reduced pressure to obtain BocONH(CH2)3SO2CH2COOH. S4: Dissolve 25.4 kg of BocONH(CH2)3Si(OC2H5)3 obtained in S1 in 240 L of anhydrous tetrahydrofuran, and slowly add 1.49 kg of deionized water in an ice-water bath at 0 °C to hydrolyze 1 part of ethoxy to obtain BocONH(CH2)3Si(OC2H5)2OH. Remove trace amounts of water immediately after the reaction is complete. S5: Take 25.0 kg of BocONH(CH2)3Si(OC2H5)2OH, cool it to -10~0℃, and add 11.0 kg of oxaloyl chloride and 0.35 kg of DMF to obtain BocONH(CH2)3Si(OC2H5)2Cl. After concentrating and removing impurities at 0~5℃, dissolve it in anhydrous dichloromethane and add 15.8 kg of anhydrous triethylamine. Add it dropwise to the 24.7 kg of BocONH(CH2)3SO2CH2COOH obtained in S3 to obtain the silicon ester product. S6: Dissolve 37.8 kg of the silicone ester product obtained in S5 in 280 L of anhydrous acetonitrile, and distill under reduced pressure under nitrogen protection to obtain the degradation promoter; S7: The degradation promoter is used as the core and fed into a fluidized bed coating machine. Molten liquid urea is atomized and sprayed into the fluidized bed coating machine at an atomization pressure of 0.45 MPa to form a core of 1.8 wt% degradation promoter and 93 wt% slow-release nitrogen source. After the particles cool and solidify, the biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The mass ratio of biodegradable polyamide, dichloromethane and ethanol in the coating solution is 12:75:12. The solution is atomized and sprayed onto the outer surface of the inner layer of urea to form a slow-release film of 5.2 wt%, thus obtaining slow-release nitrogen source particles. S8: Thoroughly mix, sieve, and grade the following ingredients: 36 kg slow-release nitrogen source granules, 24 kg ammonium dihydrogen phosphate, 22 kg potassium chloride, 10 kg ammonium sulfate, 4 kg magnesium sulfate monohydrate, 0.8 kg zinc sulfate monohydrate, 0.9 kg borax, 6 kg magnesium phytate-bridged alginate nitrogen-supported zeolite, and 5 kg zinc tannate complexed chitosan nitration inhibitor microcapsules; S9: Transfer the graded and premixed materials into a low-speed horizontal mixer, control the stirring speed at 35 r / min, add 0.2 kg of fertilizer-specific anti-caking agent, continue mixing for 12 min, and screen the output to obtain particles of 2.0~4.0 mm to obtain a long-acting slow-release blended fertilizer.

[0043] Performance testing: 1. Nitrogen content: The nitrogen content of the materials obtained in Examples 1-3 and Comparative Examples 1-4 was determined by the method in GB / T 8572-2010 "Determination of total nitrogen content in compound fertilizers by distillation titration". The experimental results are shown in Table 1.

[0044] 2. Phosphorus content: The available phosphorus content of the materials obtained in Examples 1-3 and Comparative Examples 1-4 was determined by the method in GB / T 8573-2017 "Determination of Available Phosphorus Content in Compound Fertilizers". The experimental results are shown in Table 1.

[0045] 3. Potassium content: The potassium content of the materials obtained in Examples 1-3 and Comparative Examples 1-4 was determined by the method in GB / T 8574-2024 "Determination of Potassium Content in Compound Fertilizers". The experimental results are shown in Table 1.

[0046] 4. Particle size: The particle size of the materials obtained in Examples 1-3 and Comparative Examples 1-4 was determined by the method in GB / T 24891-2010 "Determination of Particle Size of Compound Fertilizers". The experimental results are shown in Table 1.

[0047] 5. Soil degradation performance: The materials obtained in Examples 1-3 and Comparative Examples 1-4 were tested for degradation performance of the coating material and UV-944 under aerobic soil conditions according to the methods in GB / T 31270.1-2014 "Chemical Pesticide Environmental Safety Evaluation Test Guidelines Part 1: Soil Degradation Test".

[0048] Table 1. Performance tests of each embodiment and comparative example

[0049] Data Analysis: refer to Figure 1The synthesis route diagram is provided, and all examples employ the complete synthesis method. Example 1 represents the lower limit range of the raw material formulation. The synthesis of the degradation accelerator follows the process of Boc amino protection, sulfide oxidation to sulfone, monoethoxy hydrolysis and acyl chloride to silicon ester, and microwave deprotection. The resulting degradation accelerator molecule exposes free amino groups at both ends. These amino groups can form numerous intermolecular hydrogen bonds with the amide groups of the molten urea molecules, eliminating the interfacial tension between the solid core of the degradation accelerator and the molten urea coating layer at the molecular interface level. The two-phase interface is fully wetted, and after urea solidification, there are no interfacial gaps, voids, or microcracks. This allows for successful high-temperature spraying, cooling curing, and low-temperature cooling in fluidized beds. Rapid mixing and stirring ensure uniform stress distribution within the slow-release nitrogen source particles, reducing the likelihood of particle breakage. Example 2 represents the upper limit of the formulation for the amount of each basic fertilizer. Increasing the urea content in the system increases the thickness of the urea inner layer in the slow-release nitrogen source particles. The free amino groups at both ends of the degradation promoter form hydrogen bonds with the urea, and the increased urea layer thickness slightly increases the internal cooling shrinkage stress of the particles, resulting in a slightly lower particle strength than in Example 1. Example 3 uses a feeding ratio in the middle of the formulation range. This ratio produces fewer fertilizer byproducts, ensuring the nitrogen source particles have a complete structure. The moderate nitrogen source content also results in moderate particle integrity during cooling shrinkage.

[0050] Regarding nitrogen content, in Comparative Example 1, the poor compatibility between the core and urea interface led to the breakage of the slow-release nitrogen source particles, resulting in the production of urea-containing fine powder. This fine powder was removed during the final sieving, causing the loss of nitrogen source fragments. In Comparative Example 2, the absence of sulfone groups meant that the thioether bonds did not react with the nitrogen-containing components, preventing ammonia decomposition and volatilization. In Comparative Example 3, excessive hydrolysis and silanol cross-linking agglomeration occurred during the synthesis of the degradation promoter, having a relatively small impact on the loss caused by urea hydrolysis, ammonia volatilization, and salt decomposition. The agglomerated core caused uneven coating of the slow-release nitrogen source particles, resulting in cracks and subsequent breakage of the nitrogen source particles, thus reducing the nitrogen content. In Comparative Example 4, the Boc group blocking the amino group resulted in insufficient hydrogen bonds at the interface between the degradation promoter and the nitrogen source, causing partial micro-cracks in the slow-release nitrogen source particles. A small amount of particle breakage and a small amount of urea fine powder were removed during sieving, leading to partial loss of the nitrogen source.

[0051] Regarding phosphorus content, in Comparative Example 1, the ammonium phosphate crystals were crushed in the fertilizer, and were mechanically crushed into fine powder and removed by sieving, but the loss of phosphorus was limited. In Comparative Example 2, the sulfone bond and sulfone functional group did not react with phosphate, so the chemical form of phosphorus was not affected, and therefore the phosphorus content was almost unaffected. In Comparative Example 3, the phosphorus was contained in ammonium dihydrogen phosphate as independent particles, with no risk of chemical passivation. Under the violent mechanical impact of the material, some ammonium dihydrogen phosphate was broken, causing a small amount of physical loss and reducing the phosphorus content. In Comparative Example 4, the Boc group did not react with phosphate, and the available phosphorus in ammonium dihydrogen phosphate was not passivated or deactivated. Only a small number of particles were broken in the system, the production of fine ammonium phosphate powder was small, and the change in phosphorus content was small.

[0052] Regarding potassium content, in Comparative Example 1, the potassium element comes from inorganic potassium chloride crystals. Due to the high hardness of potassium chloride and its difficulty in grinding, only some particles are refined, so the change in potassium content is relatively limited. In Comparative Example 2, the sulfide does not act on the potassium chloride crystals and does not cause potassium ion fixation, so its impact on potassium content is weak. In Comparative Example 3, potassium chloride has high chemical stability and only suffers slight loss under high crushing conditions. In Comparative Example 4, the protection of Boc does not react with potassium chloride, resulting in a small loss of potassium content.

[0053] In terms of particle size, Comparative Example 1 did not use a Boc group to protect the amino group. The free primary amino group is a highly active site. During the multi-step synthesis reaction of chloroacetic acid substitution in S2 and acyl chloride-silicone ester bonding in S5, the amino group will undergo intramolecular and intermolecular side reactions with the carboxyl group and acyl chloride, respectively, resulting in amidation crosslinking to generate oligomer byproducts. The yield of the degradation promoter of the target structure decreased significantly. The byproduct molecules lacked a regular double-terminated amino structure and could not form a high-density hydrogen bond network with molten urea. The interfacial compatibility between the core particles of the degradation promoter and the urea phase was significantly reduced, and a large number of voids and cracks appeared at the interface between the two phases. In Comparative Example 2, the thioether in the molecule was not oxidized to generate a sulfone group during the synthesis. The reaction sites of the additive with thioether functional group are concentrated in Sulfur atoms do not act on amino or siloxane structures and do not participate in the conversion of nitrogen, phosphorus, and potassium components in fertilizers. Sulfone groups cause the coating membrane to degrade after nitrogen fertilizer is applied to the soil. In Comparative Example 3, excessive hydrolysis occurs, and the resulting silanols have extremely strong chemical activity, easily leading to silanol-silanol intermolecular dehydration condensation, siloxane crosslinking, and oligomer agglomeration, resulting in irregular morphology of the agglomerated core particles. Comparative Example 4 lacks microwave de-Boc treatment, and the Boc groups are blocked, preventing the amino groups from being exposed and free. After losing the free amino groups, the hydrogen bond sites formed between the degradation agent core and urea decrease, the hydrogen bond network density at the two-phase interface decreases, and the interfacial wetting ability weakens. At the same time, due to the influence of steric hindrance, it hinders the formation of hydrogen bonds between the degradation agent molecules and urea, resulting in some microcracks.

[0054] Regarding the degradation half-life of the coating materials, the degradation half-lives of the coating materials in Examples 1-3 ranged from 86.5 to 88.3 days, indicating that the degradation promoter can effectively accelerate the degradation process of the coating materials and UV-944 light stabilizer in the soil, avoiding long-term residues of the coating materials and light stabilizer in the soil. In Comparative Example 1, the amino group was not protected by Boc. During the synthesis process, the amino group, carboxyl group, and acyl chloride underwent intramolecular / intermolecular side reactions, generating amidated oligomers. The yield of the target degradation promoter decreased significantly. The molecular structure lacked regular double-terminated amino groups and siloxane anchoring groups, and the degradation promoter could not be effectively covalently grafted into the coating matrix. It was lost in the soil with water migration, and the degradation half-life was extended to 152.6 days. In Comparative Example 2, the hydrogen peroxide oxidation step was missing, and only thioether bonds were retained in the molecule instead of sulfone groups. Thioethers do not have the properties of hydrogen peroxide in the soil environment. The ability of free radicals to attack the polyamide backbone and the active sites of UV-944 resulted in almost no degradation of the coating material and no significant degradation of UV-944, confirming that the sulfone group is the key active group for the degradation promoter to exert its degradation function. In Comparative Example 3, excessive deionized water led to excessive hydrolysis of siloxanes, and intermolecular dehydration condensation crosslinking of silanol groups. The degradation promoter agglomerated into irregular large particles, and the effective functional groups were embedded and passivated. Its dispersibility and anchoring efficiency in the coating were significantly reduced, resulting in a degradation half-life of 124.8 days. In Comparative Example 4, the lack of microwave de-Boc treatment resulted in the amino groups being blocked by tert-butoxycarbonyl groups and unable to be exposed. The degradation promoter molecules lacked free amino groups at both ends, and insufficient hydrogen bonding with the urea interface led to microcracks in the particles. At the same time, the blocked amino groups could not form acid-base dual catalytic sites in the soil, and the degradation half-life was extended to 102.3 days.

[0055] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A long-acting, slow-release blended fertilizer, characterized in that, Includes the following raw material components by weight: 28-36 parts by weight of urea, 18-24 parts by weight of ammonium dihydrogen phosphate, 16-22 parts by weight of potassium chloride, 6-10 parts by weight of ammonium sulfate, 2-4 parts by weight of magnesium sulfate monohydrate, 0.3-0.8 parts by weight of zinc sulfate monohydrate, 0.4-0.9 parts by weight of borax, 3-6 parts by weight of magnesium phytate-bridged alginate nitrogen-loaded zeolite, 2-5 parts by weight of zinc tannate complexed chitosan nitration inhibitor microcapsules, 0.2-0.6 parts by weight of anti-caking agent, 1.2-2.5 parts by weight of biodegradable polyamide, and 0.08-0.25 parts by weight of degradation promoter; The specific preparation method of the degradation promoter is as follows: S1: Dissolve 3-mercapto-1-propane and KH-550 in dichloromethane at 0~5℃, and add di-tert-butyl dicarbonate and triethylamine respectively. Stir continuously at 500~1000 rpm for 1 hour, wash with water and concentrate to obtain Boc-ONH-(CH2)OC2H5-SH and BocONH(CH2)3Si(OC2H5)3; S2: Dissolve the obtained Boc-ONH-(CH2)3-SH in anhydrous ethanol and add chloroacetic acid. Add potassium carbonate as a base to adjust the pH of the system to 8-9. Heat the system to 40-50℃ and stir continuously for 1 hour. Finally, adjust the pH of the system to 7.5-8 and extract and concentrate to obtain BocONH(CH2)3SCH2COOH. S3: Dissolve BocONH(CH2)3SCH2COOH in glacial acetic acid, control the temperature of the system at 30℃ and slowly add sufficient hydrogen peroxide dropwise, and stir continuously at a speed of 500~1000 rpm until the reaction is complete. Remove the solvent under reduced pressure to obtain BocONH(CH2)3SO2CH2COOH. S4: Dissolve the BocONH(CH2)3Si(OC2H5)3 obtained in S1 in anhydrous tetrahydrofuran, slowly add 1.0~1.2 eq of deionized water in an ice-water bath at 0℃, hydrolyze 1 part of ethoxy to obtain BocONH(CH2)3Si(OC2H5)2OH, and immediately remove trace amounts of water after the reaction is complete. S5: BocONH(CH2)3Si(OC2H5)2OH is cooled to -10~0℃ and oxaloyl chloride and DMF are added to obtain BocONH(CH2)3Si(OC2H5)2Cl. After concentrating and removing impurities at 0~5℃, it is dissolved in anhydrous dichloromethane and 2.2 eq of anhydrous triethylamine is added. This is then added dropwise to the BocONH(CH2)3SO2CH2COOH obtained in S3 to obtain the silicon ester product. S6: Dissolve the silicone ester product obtained in S5 in anhydrous acetonitrile, remove Boc by microwave with lithium chloride under nitrogen protection for 1 hour, and then distill under reduced pressure to obtain the degradation promoter.

2. The long-acting slow-release blended fertilizer according to claim 1, characterized in that, The particle size of the urea, ammonium dihydrogen phosphate, potassium chloride, ammonium sulfate, magnesium sulfate monohydrate, and zinc sulfate monohydrate is 2.0~4.0 mm.

3. The long-acting slow-release blended fertilizer according to claim 1, characterized in that, The main chain of the biodegradable polyamide contains both aliphatic amide segments and aliphatic ester segments.

4. The long-acting slow-release blended fertilizer according to claim 1, characterized in that, The 3-mercapto-1-propane and di-tert-butyl dicarbonate were mixed in a molar ratio of 1:(1~1.2) and KH-550 and di-tert-butyl dicarbonate were mixed in a molar ratio of 1:(1~1.2).

5. A long-acting, slow-release blended fertilizer according to claim 1, characterized in that, The amount of oxaloyl chloride added is 1 to 1.2 eq of BocONH(CH2)3Si(OC2H5)2OH.

6. A long-acting, slow-release blended fertilizer according to claim 1, characterized in that, The microwave Boc removal setting includes a microwave reactor power of 250~300W, a temperature control of 130~140℃, a pressure limit of 12~14bar, a stirring speed of 400~600rpm, and a microwave reaction time of 60min.

7. A method for preparing a long-acting, slow-release blended fertilizer as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) The degradation promoter is used as the core and put into a fluidized bed coating machine. Molten liquid urea is sprayed into the fluidized bed and continuously coated with the inner layer of urea on the outside of the degradation promoter particles. After the inner layer of urea is coated, the particles are cooled and solidified. The fluidized bed is kept in a fluidized state. The biodegradable polyamide is dissolved in a dichloromethane-ethanol mixed solvent to prepare a coating solution. The solution is sprayed onto the outer surface of the inner layer of urea. The solvent evaporates to form a film, resulting in slow-release nitrogen source particles with the degradation promoter core, urea coating inner layer, and biodegradable polyamide slow-release film outer layer in sequence from the inside to the outside. (2) The slow-release nitrogen source particles, ammonium dihydrogen phosphate, potassium chloride, ammonium sulfate, magnesium sulfate monohydrate, zinc sulfate monohydrate, borax, magnesium phytate-bridged alginate nitrogen-supported zeolite, and zinc tannate complexed chitosan nitration inhibitor microcapsules are thoroughly mixed, sieved, and graded for premixing. (3) Transfer the graded and premixed material into a low-speed horizontal mixer, control the stirring speed at 25~35r / min, add fertilizer-specific anti-caking agent, continue mixing for 8~12min, discharge and screen to obtain long-acting slow-release blended fertilizer.

8. The method for preparing a long-acting slow-release blended fertilizer according to claim 7, characterized in that, (1) The atomization pressure of the fluidized bed coating machine is 0.30~0.45MPa. When preparing the coating solution, the mass ratio of degradable polyamide, dichloromethane and ethanol is (8~12):(75~82):(8~12).

9. The method for preparing a long-acting slow-release blended fertilizer according to claim 7, characterized in that, (1) The obtained slow-release nitrogen source particles, from the inside to the outside, are: the core of the degradation promoter accounts for 0.5~1.8 wt% of the total mass of the slow-release nitrogen source particles, the inner layer of urea accounts for 88~93 wt% of the total mass of the slow-release nitrogen source particles, and the outer layer of the biodegradable polyamide slow-release membrane accounts for 4~9.5 wt% of the total mass of the slow-release nitrogen source particles.

10. The method for preparing a long-acting slow-release blended fertilizer according to claim 7, characterized in that, (2) Before the graded premixing, each fertilizer particle is screened to remove particles with a particle size of <2.0mm and >4.0mm. The graded premixing is to premix the slow-release nitrogen source particles with phytic acid magnesium-bridged alginate nitrogen-loaded zeolite and tannic acid zinc complexed chitosan nitration inhibitor microcapsules to obtain functional particle mixture, and then mix the functional particle mixture with the remaining basic fertilizer particles.